Managing Innovation and Standards - Wiegmann, Paul Moritz (Springer Nature, 2019)
This book provides an in-depth study of the management of standards and regulation in sustainable and radical innovation development. It considers the case of micro Combined Heat and Power (mCHP) technology. The developers of this radical innovation in the European heating sector encountered major conflicts when attempting to create or adapt standards when bringing the technology to market. Utilising rich research data and interviews with key actors, the author uses this case to derive a grounded theory on the management of standards and regulation during an innovation process. The results also have important implications for innovators, which are reflected in clear advice for practice.